Sacrococcygeal Pilonidal Sinus Diseases and Operative Management at Burn and Plastic Hospital in Duhok City - Kareem Muhammed Ahmed (Advanced Medical Journal)
Background and objectives: Pilonidal sinus diseases usually seen in young adults, carry much morbidity and patient discomfort. The management is the most critical issue in surgical treatment because it is related to postoperative morbidity and recurrence. So, this study aims to explore sacrococcygeal pilonidal sinus diseases and the operative methods achieved in Burn and Plastic hospital in Duhok City.